Cover Picture: Preparation, Structural Determination, and Characterization of Electronic Properties of Bis‐silylated and Bis‐germylated Lu3N@Ih‐C80 (Chem. Eur. J. 46/2015). Issue 46 (9th November 2015) - Kako, Masahiro; Miyabe, Kyosuke; Sato, Kumiko; Suzuki, Mitsuaki; Mizorogi, Naomi; Wang, Wei‐Wei; Yamada, Michio; Maeda, Yutaka; Olmstead, Marilyn M.; Balch, Alan L.; Nagase, Shigeru; Akasaka, Takeshi
Abstract : Exohedral derivatization of Lu3 N@ I h ‐C80 was successfully conducted by the photoreactions with disilirane and digermirane. The single‐crystal X‐ray structural analyses firmly established the 1, 4‐bis‐silylated and bis‐germylated structures, which represent rare examples of the crystallographic studies of functionalized Lu3 N@ Ih ‐C80 . The electrochemical and theoretical studies revealed that the redox properties of the bis‐silylated and bis‐germylated derivatives were remarkably altered compared to those of the parent Lu3 N@ Ih ‐C80 . For more details see the Full Paper onpage 16411 ff. by M. Kako, M. M. Olmstead, A. L. Balch, S. Nagase, T. Akasaka et al.